Democratic leadership and management practices in a rural Namibian secondary school - Mabuku, Robert Nalisa (Rhodes University, Faculty of Education, Department of Education, 2010)
The primary purpose of this research was to investigate the understanding and implementation of democratic leadership and management in schools by school managers and other members of the school community in leadership and management roles as advocated by the policy of Education for all. The study also aimed at identifying any gaps in the understanding and practice of the participants in order to enhance democratic leadership and management in schools. Qualitative research using the interpretive approach was the methodology employed in order to fulfill the intention of the study, namely to investigate the participants` experiences and understanding of democratic education leadership and management. The case study method was appropriate to understand the meanings the participants attached to their practice in their natural setting. Data were collected by using semi-structured interviews, document analysis, and observation. The sample for the study consisted of ten participants: the principal, the head of department, two School Board members, two senior teachers, two Learner Representative Council members and two class captains. The findings suggest that the participants understood and practised democratic ELM in terms of broader participation, open communication, delegation for empowerment, learning organisation, shared decision-making, shared leadership and teamwork. However, the data suggest areas of concern in the participants` understanding and implementation of the policy which could be strengthened to entrench the policy. The study recommends that education policy makers, education managers, school managers, teachers, parents and learners all work towards improving democratic ELM in schools. In order to achieve this objective, policy makers are urged to avoid ambiguity to enable all implementers to fully understand policies. Education managers could ensure school-wide training on the policy while school managers and other stakeholders should engage in self-reflection and introspection and be more proactive towards improving their own understanding and practice.
Keywords: Educational leadership -- Namibia -- Case studies; School management and organization -- Namibia -- Case studies; Education, Secondary -- Namibia -- Case studies; Educational change -- Namibia -- Case studies